Report of Committee on Improvement in Quality and Economy in Production in the Govt. of India Presses - Ministry of Works, Government of India (Ministry of Works, Government of India, 1960)
This report summarizes the findings and recommendations of Committee J, constituted in 1959 to examine the quality and economy of production in the Government of India Presses. The committee identified a significant gap between government and private presses in terms of productivity, print quality, and operational efficiency, attributing this primarily to weak supervision, ineffective management structures, inadequate training, and declining discipline. Although government presses possessed modern buildings and machinery comparable to the private sector, these assets were underutilized due to poor maintenance, lack of planning, and inefficient organizational practices. The report emphasizes the need for structural reorganization, improved supervisory control, standardized procurement, preventive maintenance, and the establishment of dedicated planning sections. It also highlights the importance of personnel development through merit-based recruitment and promotion, systematic training, and incentive schemes to motivate workers. The committee concludes that sustained improvements in quality and efficiency depend on managerial autonomy, accountability, and the creation of a quality-conscious work culture. If implemented in a coordinated and timely manner, the recommended reforms are expected to significantly enhance productivity and ensure that Government of India Presses meet growing demands without compromising standards.
Government of India Ministry of Works
Keywords: Government of India Presses; Printing Quality; Operational Efficiency; Supervisory Reform; Productivity Improvement; Plant and Machinery; Procurement Practices; Personnel Development; Incentive Bonus Scheme; Planning and Control; Preventive Maintenance; Merit-Based Promotion